h(x)=4x+3h(x+4)+7

Simple and best practice solution for h(x)=4x+3h(x+4)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h(x)=4x+3h(x+4)+7 equation:


Simplifying
h(x) = 4x + 3h(x + 4) + 7

Multiply h * x
hx = 4x + 3h(x + 4) + 7

Reorder the terms:
hx = 4x + 3h(4 + x) + 7
hx = 4x + (4 * 3h + x * 3h) + 7
hx = 4x + (12h + 3hx) + 7

Reorder the terms:
hx = 7 + 12h + 3hx + 4x

Solving
hx = 7 + 12h + 3hx + 4x

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-12h' to each side of the equation.
-12h + hx = 7 + 12h + 3hx + -12h + 4x

Reorder the terms:
-12h + hx = 7 + 12h + -12h + 3hx + 4x

Combine like terms: 12h + -12h = 0
-12h + hx = 7 + 0 + 3hx + 4x
-12h + hx = 7 + 3hx + 4x

Add '-3hx' to each side of the equation.
-12h + hx + -3hx = 7 + 3hx + -3hx + 4x

Combine like terms: hx + -3hx = -2hx
-12h + -2hx = 7 + 3hx + -3hx + 4x

Combine like terms: 3hx + -3hx = 0
-12h + -2hx = 7 + 0 + 4x
-12h + -2hx = 7 + 4x

Reorder the terms:
-7 + -12h + -2hx + -4x = 7 + 4x + -7 + -4x

Reorder the terms:
-7 + -12h + -2hx + -4x = 7 + -7 + 4x + -4x

Combine like terms: 7 + -7 = 0
-7 + -12h + -2hx + -4x = 0 + 4x + -4x
-7 + -12h + -2hx + -4x = 4x + -4x

Combine like terms: 4x + -4x = 0
-7 + -12h + -2hx + -4x = 0

Factor out the Greatest Common Factor (GCF), '-1'.
-1(7 + 12h + 2hx + 4x) = 0

Ignore the factor -1.

Subproblem 1

Set the factor '(7 + 12h + 2hx + 4x)' equal to zero and attempt to solve: Simplifying 7 + 12h + 2hx + 4x = 0 Solving 7 + 12h + 2hx + 4x = 0 Move all terms containing h to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + 12h + 2hx + -7 + 4x = 0 + -7 Reorder the terms: 7 + -7 + 12h + 2hx + 4x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 12h + 2hx + 4x = 0 + -7 12h + 2hx + 4x = 0 + -7 Combine like terms: 0 + -7 = -7 12h + 2hx + 4x = -7 Add '-4x' to each side of the equation. 12h + 2hx + 4x + -4x = -7 + -4x Combine like terms: 4x + -4x = 0 12h + 2hx + 0 = -7 + -4x 12h + 2hx = -7 + -4x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| x=(x+5)*(x*4) | | h(x)=4x+3forh(x+4)+7 | | 69+x-2=2 | | 10/15=12/x? | | y=8x-x+x+11*4 | | 0.33x-0.33=0.28x-0.14 | | 91=y/7 | | (4x-4w+7)(x-4)= | | 5x-11y=19 | | 4(x+1)=8x+2 | | -13x=-7 | | 1.2x+0.2=0.375x+3.5 | | -x=-9-5 | | (v+7)(v-5)=0 | | X+Y+11Y=26 | | -5t+7=11t+25 | | 5=3n^3/2 | | 2(5x-1)=-6 | | 4x/3-7=19 | | 2(5x-1)=6 | | y=100x+3+506x-x | | (2/3)×7 | | 4(x+6)=-5(x+1)+3(4-x)+12x+17 | | d/4=0.3 | | (4y-2)/5=(y-6)/4 | | 5(4x+3)+3x+3=41 | | 9x-8y=-67 | | 19.5-x=7.2 | | 12x^2+24+5=4x+5 | | y=x+x+20 | | 7x+14y=49 | | 8(-7)=6(-7)-14 |

Equations solver categories